Public Transport Service Quality and Community Satisfaction Level in Bali, Indonesia - Purwadana, I Made (Universitas Negeri Malang, 2019)
ABSTRACT This study aims to analyze the effect of transport performance and bus crew performance on the quality of Trans Sarbagita transportation services in Bali Province. This study combines a descriptive analysis techniques and structural equations with alternative PLS SEM. The findings showed that the performance of transport and performance of the bus crew had a positive and significant effect on the quality of Trans Sarbagita transportation services in the Province of Bali. Transportation performance, bus crew performance and service quality have a significantly affects on the satisfaction level of Trans Sarbagita users in Bali Province. Transport performance and bus crew performance indirectly influence the level of satisfaction through the quality of Trans Sarbagita services in Bali Province. Based on the results of the study, a more comprehensive study is needed in the development of Trans Sarbagita public transportation to realize service quality and maximum level of satisfaction. Keywords: Transport Performance, Community Satisfaction, Service Quality, and Satisfaction Level